2019
DOI: 10.3171/2018.7.peds18297
|View full text |Cite
|
Sign up to set email alerts
|

Distress and psychosocial risk in families with newly diagnosed pediatric brain tumors

Abstract: OBJECTIVEHospitalization for a newly diagnosed pediatric brain tumor is an extremely stressful time for a family, but this period has not been the focus of rigorous study. The purpose of this study was to quantify distress and psychosocial risk in this population to improve psychosocial care delivery.METHODSThe authors administered the National Comprehensive Cancer Network Distress Thermometer (DT) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…In our model, we did not include the caregiver's level of education as this variable is inherently included within our PAT questionnaire. Our results are in accordance with another recent study by Rocque et al 42 that investigated children with brain tumours. As in our study, demographic factors were not found to be significantly predictive of PAT scores.…”
Section: Open Accesssupporting
confidence: 94%
“…In our model, we did not include the caregiver's level of education as this variable is inherently included within our PAT questionnaire. Our results are in accordance with another recent study by Rocque et al 42 that investigated children with brain tumours. As in our study, demographic factors were not found to be significantly predictive of PAT scores.…”
Section: Open Accesssupporting
confidence: 94%
“…The psychosocial effects of a pediatric brain tumor diagnosis and treatment course impact the entire family unit, including the child’s parental figures [1,2,3]. Parental caregiver distress is notably higher in pediatric brain tumor diagnoses than for parents of children with other forms of cancer [4]. The multiple psychosocial impacts of childhood brain cancer are noted to have lasting and late effects, not only for survivors of childhood brain tumors, but also for their parents [1,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study based on first-hand accounts of healthcare professionals taking care of children with brain tumors in a neurosurgery unit. Nonetheless, some of the themes emerging from our data can be fruitfully confronted with results coming from different pediatric oncology settings (Zander et al, 2010;Taylor and Aldridge, 2017;Rocque et al, 2018;Slater et al, 2018;Nicklin et al, 2021). Morris and Morris (2017) undertook a qualitative study with the aim of exploring the experiences of the medical staff in a very stressful pediatric setting, characterized by high staff burnout, anxiety, and high turnover rates, namely in a pediatric bone marrow transplant unit.…”
Section: Discussionmentioning
confidence: 99%